Integration by parts

∫u dv = u·v - ∫v du

Demonstration: There is a formula for the differentials analogue to the formula of the derivatives (u·v)’ = u·v’ + u’·v

d(u·v) = du · v + u · dv

then if we integrate it

∫d(u·v) = ∫v du+∫u dv and if we work out:

∫u dv = u·v - ∫v du  QED




 Exercise. Solve the following integrals:

a) ∫x·cosx dx =

b) ∫x3ex dx =





Solutions: a) x·sinx + cosx + k; b) ex(x3 - 3x2 + 6x -6) + k


Licensed under the Creative Commons Attribution Non-commercial Share Alike 3.0 License